Expanding Square Brackets | Algebra | Maths
In this video we’re going to have a look at how to expand squared brackets. You should already know how to expand double brackets by multiplying each term in the first bracket, by each term in the second bracket and then simplifying.
EXAMPLE: (x - 4)(x + 3) = x^2 - 4x + 3x - 12 = x^2 - x - 12. For expanding squared brackets,
EXAMPLE: (x - 5)^2. Just like 3^2 means 3 X 3, the squared bracket here means the bracket times the bracket.
EXAMPLE: (x - 5)^2 = (x - 5)(x - 5) = x^2 - 5x - 5x + 25 = x^2 - 10x - 25.